Coexistence of Psoriatic Spondyloarthropathy and Gout: A Case Report - Yasemin Turan,; Zehra Kocaağa,; Hikmet Koçyiğit,; Alev Gürgan,; Bayram Korhan, (Archives of Rheumatology, 2009)
We present a 60-year-old male patient who had concurrent psoriatic spondyloarthropathy and gout, which has not been reported in the literature previously. In this paper, the clinical and radiological features of both rheumatic diseases are discussed in light of the recent literature. (Turk J Rheumatol 2009; 24: 159-62)